SIFAT SENSORIS ASAP CAIR TEMPURUNG KELAPA HASIL ADSORPSI PADA ZEOLIT - Syahraeni Kadir; Purnama Darmadji; Chusnul Hidayat; Supriyadi Supriyadi (Universitas Tadulako, 2014)
Liquid smoke has a strong and pungent distinctive aroma caused some contributors compounds in these products, among others, phenolic, carbonyl and acid. Adsorption using zeolites in this study aimed to reduce the levels of hard pungent aroma compounds contributors so that liquid smoke can be accepted by consumers. Various pH zeolite ie 2, 3, 4, 5 and 6 are used as adsorbent liquid smoke where the fraction of adsorption results sensory analyzed by 20 panelists selected. Liquid smoke fraction was selected based on the results of sensory testing further analyzed using GC-MS and then analyzes the data using analysis of variance (ANOVA) with SPSS software version 16, followed by Duncan range test level of 1%. The results showed that as many as 14 fractions were tested for sensory worth of 25 fractions of liquid smoke coconut shell results in zeolite adsorption pH 2-6 where 11 other factions have a scent that is